Anti-diabetic activity of PUFAs-rich extracts of Chlorella pyrenoidosa and Spirulina platensis in rats. (June 2019) - Wan, Xu-zhi; Li, Tian-tian; Zhong, Ru-ting; Chen, Hong-bin; Xia, Xue; Gao, Lu-ying; Gao, Xiao-xiang; Liu, Bin; Zhang, Hui-ying; Zhao, Chao
Abstract: The contributions to hypoglycemic function and gut microbiota regulation by water and ethanol extracts of the microalgae Chlorella pyrenoidosa and Spirulina platensis were determined. An ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry analysis indicated that most of the compounds in the 55% ethanol extracts of C. pyrenoidosa (CP55) and S. platensis (SP55) were polyunsaturated fatty acids. After an 8-week high-fat high-sucrose diet with C. pyrenoidosa and S. platensis supplementation, glucose tolerance was improved, and the composition of the gut microbiota was altered. The diversity of the gut bacterial community was evaluated using 16S rRNA gene pyrosequencing. C. pyrenoidosa supplementation increased the abundance of Ruminococcus, Parasutterella, and Erysipelotrichacea and decreased the abundance of Lactobacillus, Turicibacter, and Blautia ; S. platensis supplementation increased the abundance of Oscillibacter, Parasutterella, and Alloprevotella and decreased the abundance of Turicibacter . Moreover, Erysipelotrichacea and Ruminococcus were uniquely increased in C. pyrenoidosa treatment groups. Thus, CP55 and SP55 may be developed as effective natural food materials for preventing diabetes, and Ruminococcus may play a vital role in the treatment of diabetes.